Ocorrência do metapneumovírus humano nas infecções respiratórias agudas em estados da região nordeste do Brasil - SILVA, Allan Kaio (Universidade Federal do Pará, 2015)
The respiratory tract illnesses are responsible by a significant rate of laborer absenteeism as well like by elevated indices of morbidity and death, between which the acute respiratory infections (ARI) represent the bigger complaints in the medical-ambulatory service in world. The viruses are considered the main etiologic agents of ARI, acting is like main pathogen or prepossess the secondary bacterial infections, among them finds the Human Metapneumovirus (HMPV). This virus was identified in 2001 presenting as an important causal agent of ARI acquired in the community. It is a cosmopolitan virus that causes similar respiratory illnesses to the Respiratory Syncytial Virus. In Brazil, reports are relatively scarce about the occurrence of the HMPV in the population. The objective of this study is to investigate the occurrence of Human Metapneumovírus (HMPV) in patients with clinical diagnosis of acute respiratory infection (ARI) in the Northeast Region of Brazil. Between the period of June 2009 to September 2010, patients from basic attention unit or hospital units services of five states of Northeast Region, were submitted the collection of specimens for detection from techniques of molecular biology. Statistical analyses were utilized for sample choice (545) and handling of the results obtained. The study showed a positivity of 4,7% for HMPV, without the existence of a specific age group for the occurrence of infection. A predominance of the female sex between the positive cases occurred, however, without statistical meaning. The peak of positivity for the virus (n=16) happen in the third quarter of the year in all States investigated. In this study, was possible describe the occurrence of HMPV in the Northeast Region, affecting patients with acute respiratory infection like accompanied in basic attention as hospitalized, that filled clinical criterion for Severe Acute Respiratory Syndrome.